Pemanfaatan Media Animasi untuk Meningkatkan Hasil Belajar Siswa pada Materi Konsep Pembelahan Sel Siswa Kelas XII IPA SMA Negeri 1 Bunut - Yeviliona, Merina (Tematik: Jurnal Penelitian Pendidikan Dasar, 2023)
This research focuses on augmenting class learning creativity through a comprehensive classroom action research initiative conducted in two cycles. The meticulous process involves planning, implementing actions, observing, and reflecting. The research cohort encompasses 31 students in the twelfth grade at SMA Negeri 1 Bunut. Notably, the findings underscore the instrumental role of animation media in enhancing student learning outcomes in the domain of biology. Conclusively, (1) the integration of animation media amplifies student engagement during the learning process by a commendable 75%, and (2) it substantially elevates the completeness of student learning outcomes in biology by an impressive 75%. This research contributes to the evolving landscape of educational methodologies, highlighting the efficacy of animation media in cultivating dynamic and effective learning environments. The overwhelmingly positive response from both students and educators reaffirms the significance of employing innovative multimedia tools for optimal learning experiences.